SHILLER, R. J. (2012). Finance and the Good Society (ICADE. Revista de la Facultad de Derecho, 2014)
Autor: Robert J. ShillerEditorial: Princeton University Press,abril, 2012.
Keywords: Shiller; society; sociedad; good